Multiple melanomas after treatment for Hodgkin lymphoma in a non-Dutch p16-Leiden mutation carrier with 2 MC1R high-risk variants - Figl, Adina; Ugurel, Selma; Gast, Andreas; Hemminki, Kari; Kumar, Rajiv; Schadendorf, Dirk (Archives of dermatology, 2007)
BACKGROUND: A 19-base pair germline deletion in exon 2 of the CDKN2A (cyclin-dependent kinase inhibitor 2A) gene (Leiden mutation) has been detected in Dutch families with familial melanomas. The penetrance of CDKN2A mutations varies widely and is influenced by environmental and unrelated genetic factors such as variants in the MC1R gene. - OBSERVATIONS: We describe a 25-year-old German woman who developed 8 invasive melanomas and 6 in situ melanomas after radiation therapy and polychemotherapy for Hodgkin lymphoma. Genetic testing revealed a constitutional CDKN2A Leiden mutation in the proband and her sister, mother, and mother's sister. The proband also carried high-risk MC1R variant alleles R151C and R160W, which she had inherited from her father and her mother, respectively. The less affected mutation carrier sister did not have high-risk MC1R variant alleles. Analysis of DNA from paraffin-embedded tissues showed loss of heterozygosity at CDKN2A loci in all 3 melanomas studied but not in Hodgkin lymphoma. The pedigree revealed several types of cancers on both sides of the family, but no Dutch ancestors were found. No mutations in the CDK4, B-raf, and N-ras genes were detected either in the germline or in tumors from the patient. - CONCLUSION: This study shows the variability of the penetrance of the CDKN2A Leiden mutation within the same family, which could be due to genetic or exogenous factors.
Gesehen am 05.02.2021